Upaya Meningkatkan Keaksaraan Awal Melalui Media Kotak Pintar Pada Anak Usia Dini - Ziyadaturrohmah, Annisa; Tanfidiyah, Nur (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The problem in this study is about children's early literacy skills that have not developed optimally in pre-reading activities. The media used by smart boxes can be used as a way to help early literacy skills. The aim to be achieved in this study is to improve the early literacy skills of children aged 5-6 years through smart box media in group B2 BA Aisyiyah Menuran. The informants in this study were the principal and class teacher. Data collection was carried out using interviews, observation, documentation, and performance tests. The data that has been collected is analyzed using a model developed by Miles and Huberman which consists of four components, namely data condensation, data reduction, data presentation and conclusion drawing. The results of this study indicate that smart box media can improve early literacy skills in early childhood. The increase can be seen from the scores obtained by students, at the pre-cycle stage there were 7.69% of students who could be said to be complete, then in cycle I it increased to 46.15% of the number of students, the value of student completeness increased again in cycle II to 84.61%.